Comparative study between laparoscopic common bile duct exploration and endoscopic retrograde cholangiopancreatography plus laparoscopic cholecystectomy for choledocholithiasis - Salem, Mohamed Mohsen; Esmat, Mohamed Emad; Hassan, Ahmed Mohamed Abdelaziz; Amer, Yaser; Abdelaziz, Hisham; Rady, Mahmoud (International Surgery Journal, 2019)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) with consequent laparoscopic cholecystectomy (LC) has been the favored approach for the treatment of choledocholithiasis for a long time; however recently, laparoscopic common bile duct exploration (LCBDE) has been offered to patients with suspected choledocholithiasis. Objective and aim of this work was to compare the efficacy, safety, and the surgical outcomes of LCBDE with ERCP followed by LC and determine the most appropriate approach for patients with choledocholithiasis. Methods: A prospective clinical study was carried out from March 2017 to September 2018. It included 50 patients with cholecysto-choledocholithiasis who were divided into two groups: group A (25 patients) included patients who underwent transcystic LCBDE and stone extraction with LC in one stage, and group B (25 patients) included patients who underwent ERCP followed by LC in two stages. The common bile duct (CBD) stone clearance rate, postoperative bile leakage, postoperative morbidity, mortality, overall hospital stay, and patient satisfaction were analyzed. Results: LCBDE and ERCP+LC were similar in terms of clearance rate, operative time, postoperative complications, retained CBD stones, and postoperative length of stay, but there was a significant difference in number of procedures and patient satisfaction. Conclusions: Although both approaches have equivalent success rates, LCBDE is better in terms of fewer procedures, and better satisfaction compared with ERCP + LC. Our study suggests that one-stage management is the treatment of choice for patients with cholecysto-choledocholithiasis.